EKSTRAKSI ALUMINA OKSIDA ( Al2O3) DARI TANAH LIAT DENGAN VARIABEL SUHU DAN KONSENTRASI ASAM SULFAT - Khairun Nisah (Lantanida Journal, 2016)
In this study used clay as raw material for making aluminum oxide using sulfuric acid as pelarut.Penelitian also aims to obtain sulfuric acid concentration and reaction time is best, where the variable used is the concentration of sulfuric acid ( 60 % , 70 % and 80 % ) and reaction time ( 40 minutes , 50 minutes and 60 minutes). The results showed that the greater the concentration of sulfuric acid , the levels of aluminum oxide obtained will be greater and greater the heating period , the levels of aluminum oxide obtained will also be greater . Optimum results obtained in 80% sulfuric acid concentration and reaction time 60 minutes.